Small, Dense Low-Density Lipoprotein-Cholesterol and Atherosclerosis: Relationship and Therapeutic Strategies - Jin, Xiao; Yang, Shengjie; Lu, Jing; Wu, Min (Frontiers in Cardiovascular Medicine, 2022)
Low-density lipoprotein cholesterol (LDL-C) plays an important role in the formation, incidence, and development of atherosclerosis (AS). Low-density lipoproteins can be divided into two categories: large and light LDL-C and small, dense low-density lipoprotein cholesterol (sdLDL-C). In recent years, an increasing number of studies have shown that sdLDL-C has a strong ability to cause AS because of its unique characteristics, such as having small-sized particles and low density. Therefore, this has become the focus of further research. However, the specific mechanisms regarding the involvement of sdLDL-C in AS have not been fully explained. This paper reviews the possible mechanisms of sdLDL-C in AS by reviewing relevant literature in recent years. It was found that sdLDL-C can increase the atherogenic effect by regulating the activity of gene networks, monocytes, and enzymes. This article also reviews the research progress on the effects of sdLDL-C on endothelial function, lipid metabolism, and inflammation; it also discusses its intervention effect. Diet, exercise, and other non-drug interventions can improve sdLDL-C levels. Further, drug interventions such as statins, fibrates, ezetimibe, and niacin have also been found to improve sdLDL-C levels.